Biodegradable composites with improved barrier properties and transparency from the impregnation of PLA to bacterial cellulose membranes. Issue 28 (9th April 2016) - Urbina, Leire; Algar, Itxaso; García‐Astrain, Clara; Gabilondo, Nagore; González, Alba; Corcuera, MaAngeles; Eceiza, Arantxa; Retegi, Aloña
ABSTRACT: Poly(lactic acid) (PLA) was impregnated in bacterial cellulose (BC) membranes. BC/PLA films were prepared by solvent casting and mechanical, optical and barrier properties, and biodegradation process were investigated. The transparency of processed films was higher than that of neat BC and increased with PLA content. Moreover, the incorporation of PLA to BC enhanced significantly the water vapor barrier properties of the BC membranes. The bionanocomposites contained a high percentage of cellulose due to the impregnation method that leads to the film with a BC content of 94%, which practically maintains the excellent mechanical properties of BC. However, when increasing the PLA content in the bionanocomposites the mechanical properties decreased slightly with respect to BC. Biodegradation under real soil conditions was determined indirectly through the study of the visual degradation and disintegration, demonstrating that the bionanocomposites were degraded faster than the neat PLA. The successful production of BC/PLA bionanocomposites suggested the possible application of them for active food packaging. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43669. Abstract :